The roadmap: examining the impact of a systematic goal-setting program for collegiate women's tennis players - Vidic, Z.; Burton, D. (The Sport Psychologist, 2010)
This study assessed the impact of an 8-week goal-setting program on the motivation, confidence and performance of collegiate women tennis players using a quasi-experimental pretest-posttest study design. This goal-setting program used the `roadmap` concept; a unique systematic approach to goal-setting that focused on setting coordinated long-, intermediate-, and short-term goals. Participants consisted of six female Division I collegiate tennis players who completed seven instruments to assess intervention effectiveness. Over the 8-week intervention, all 6 players demonstrated improvements in motivation, confidence and performance measures, particularly on targeted variables. Qualitative results further strengthen support for intervention success, with all six athletes consistently reporting that goal-setting was beneficial in enhancing their motivation, confidence and performance.